Double-Lumen vs Small-Bore Pigtail Catheter for Pleural Effusion: Which is Superior? - Siagian, Novi Andriani; Soeroso, Noni Novisari; Bihar, Syamsul; Ashar, Taufik (Jurnal Respirasi, 2025)
Introduction: Pleural effusion is associated with a high mortality rate. Tube thoracostomy remains the standard treatment. Despite this, double-lumen catheters, typically used for central venous access, are infrequently employed for pleural drainage. This study compared the characteristics of patients undergoing double-lumen catheter versus pigtail catheter placements for pleural effusion. Methods: A retrospective cross-sectional study was conducted on adult patients at Prof. Dr. Chairuddin Panusunan Lubis Universitas Sumatera Utara Hospital, Haji Adam Malik General Hospital, and St. Elisabeth Hospital, Medan, from September 2022 to April 2024. This study analyzed patient demographics and clinical presentations for those receiving either catheter type. Results: The mean age of patients with double-lumen catheters was 58.21 years old, while those with pigtail catheters averaged 54.9 years old. Patients with double-lumen catheters frequently presented with a combination of shortness of breath, cough, and chest pain, while those with pigtail catheters primarily reported shortness of breath. Both groups predominantly exhibited exudative pleural effusions. Radiological evaluations indicated moderate pleural effusion was most common in both groups, with thoracic ultrasound revealing fluid volumes between 500 and 2,000 cc. Conclusion: Double-lumen catheters are more frequently utilized for moderate to massive pleural effusion, whereas pigtail catheters are typically reserved for moderate cases. The choice of catheter depends on the patient's condition, the underlying cause of the effusion, and radiological findings.